The Impact of the Metabolic Syndrome Severity on the Appearance of Primary and Permanent DNA Damage - Mirta Milić; Luka Kazensky; Martina Matovinović (Medicina)
The prevalence of metabolic syndrome (MetS) worldwide is rapid and significant on a global scale. A 2022 meta-analysis of data from 28 million individuals revealed a global prevalence of 45.1%, with notably higher rates in the Eastern Mediterranean Region and the Americas, particularly in high-income countries. MetS is associated with impaired antioxidant defense mechanisms, resulting in the excessive generation of reactive oxygen and nitrogen species (RONS) and elevated levels of DNA damage. Unrepaired damage can lead to DNA base changes, chromosomal mutations, genomic loss and instability, and disrupted gene and protein expression. Such changes contribute to an increased risk of tumorigenesis, cancer progression, and mortality. The alkaline comet and micronucleus cytome assay are commonly used assays for DNA damage evaluation. The estimation of damage with those two techniques demonstrated the link between the increased risk of cancer and mortality. Incorporating these techniques in a set of biomarkers to assess the MetS severity holds promise; however, comprehensive literature reviews featuring large-scale studies integrating both assays remain scarce. This systematic review aims to integrate and critically evaluate the existing scientific literature regarding this topic.